Chemical Conservation of Paper-Based Cultural Heritage - Yueer Yan; Yi Tang; Yuliang Yang (Molecules)
Paper-based cultural heritages, represented by ancient books, archives, calligraphy, and paintings, recorded the development of human civilization [...]